2006
DOI: 10.1158/1055-9965.epi-05-0946
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expressions of Ki-67, Cyclin D1, β-Catenin, Cyclooxygenase-2, and Epidermal Growth Factor Receptor in Human Colorectal Adenoma: A Validation Study of Tissue Microarrays

Abstract: Background: Tissue microarray (TMA) holds promise as a high-throughput method for the analysis of biomarkers in tissue specimens. The validity and reliability of this method, however, may vary for different biomarkers in different tissue specimens. Objectives: In this study, we evaluated the validity and reliability of using TMA to assess biomarkers in colorectal adenomas. Methods: Sixty-three consecutive patients with colorectal adenomas were recruited in this study. Two TMA blocks were constructed using four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 27 publications
(39 reference statements)
3
33
0
Order By: Relevance
“…The missing cores in our study comprised 8.6% of the entire number of cores. This result was acceptable considering the large number of cores, and the comparison of missing core percentages of other similar studies; these core percentages deteriorated from 6.6 to 17% (11,19,20).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The missing cores in our study comprised 8.6% of the entire number of cores. This result was acceptable considering the large number of cores, and the comparison of missing core percentages of other similar studies; these core percentages deteriorated from 6.6 to 17% (11,19,20).…”
Section: Discussionmentioning
confidence: 66%
“…However, only a few studies have correlated C1 C2 C3 TMA Whole C1 C2 C3 TMA Whole Low 24 23 22 16 27 99 107 106 88 survival and clinical data with both TMA and results obtained from whole sections to establish whether data from TMAs can be reliably used for clinicopathological correlations and survival analysis (12,14). The majority of studies investigated the ability of TMA to represent whole sections in immunohistochemical studies of certain antigens as well as the optimal number of TMA cores needed to achieve acceptable representation of the specimens (6,10,(19)(20)(21). Our results showed that even one 0.6 mm TMA core represented whole sections as significantly as the score of all three TMA cores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative analysis of MIP-1α staining in the tissue microarray (TMA) was performed similar to a procedure previously described (8). Briefly, a system composed of an Olympus BX40 microscope (Olympus American, Miami, FL), a Retiga FAST 1394 color digital camera (QImaging, British Columbia, Canada), and Bioquant Nova Prime imaging analysis software (Bioquant, Nashville, TN) was used.…”
Section: Study Population and Multiplex Immunoassaysmentioning
confidence: 99%
“…Our lower loss rate (1.9% vs 4.5% to 20% in tumors) probably results from well-fixed kidney samples (Su et al 2006).…”
Section: Resultsmentioning
confidence: 61%